Elaboração de uma escala brasileira de empatia clínica - Generoso, Alexandre Tadeu Azevedo (2022)
Introduction: Empathy, which is a human beings fundamental element, has been the subject of increasing interest in medical education. In the healthcare professions context, empathy in patient care is a feature that involves understanding the patient's experiences, pain, suffering, and concerns combined with the capability to communicate these understandings and an intention to help. Despite the development of practices that stimulate empathy in medical students, a challenge present in academic life is to measure this ability. Objective: To develop and validate a Brazilian scale of empathy in the context of clinical care. Methodology: This is a mixed, quantitative and qualitative, cross-sectional study whose target audience is medical students. The initial items of the scale were made based on the literature and took into consideration interviews with the target population of the scale, as well as physicians, patients and experts on the topic. This instrument divided into: (1) Definition of the construct; (2) Definition of the scale itself; (3) Elaboration of the scale’s items; (4) Scale purification and (5) Scale validation. Result: At the end of the study, the Empathy scale elaborated contains 21 items with Likert scale responses, divided into two factors: empathic understanding and empathic action, presenting a total explained variance of 44.95%. For the psychometric analysis, it was evaluated the answers from 207 medical students from the fourth to the sixth year, using the FACTOR as an instrument for exploratory factor analysis. In this study, in general, the level of empathy of the students, measured by the proposed scale, was high (above 4 with 5 being the highest level), in both factors. It was also observed that the female sex had higher scores in the two factors of the scale. Students that pretend to follow the clinical specialty; those who presents experience of severe disease in the family and/or presents any chronic illness showed higher scores in the empathic understanding component. It was still observed that the participating medical students were divided into three distinct groups in terms of the degree of empathy shown (low, moderate and high). Conclusion: The model proposed for the Brazilian Scale of Clinical Empathy met the semantic, cultural and revealed preliminar evidence of validity, the construct is broken down into two components.